Pengaruh aplikasi Trichoderma harzianum terhadap pengendalian jamur Fusarium oxysporum pada tanaman bayam brazil (Alternanthera sissoo) - Muhamad Maulana; Aulia Rahmawati (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
Trichoderma sp. is one of the biological control agents that can be used to manage soil-borne pathogens, including Fusarium sp. This study aimed to determine the effect of Trichoderma sp. on the growth, yield, and effectiveness in controlling fusarium wilt in Brazilian spinach (Alternanthera sissoo). The experiment used a Completely Randomized Design (CRD) with four treatments and six replications. The study was conducted in the Paranet Screen House, Sidobunder Village, Puring Subdistrict, Kebumen Regency. The treatments consisted of Trichoderma sp. doses of 0 g/plant (control), 10 g/plant, 20 g/plant, and 30 g/plant. Data were analyzed using analysis of variance followed by an Honest Significant Difference (HSD) test at the 0.05 significance level. The results indicated no occurrence of fusarium wilt in plants treated with any dose of Trichoderma sp. or in the control treatment. This was presumed to be due to environmental conditions that were unfavorable for the growth of Fusarium sp. A dose of 10 g/plant of Trichoderma sp. resulted in optimal growth and yield for Brazilian spinach (Alternanthera sissoo).